Malawi : Poverty Reduction Strategy Paper; Annual Progress Report. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2006)
This paper reviews the Annual Progress Report on Malawi's Poverty Reduction Strategy (MPRS). The poverty situation remained high over the implementation period of the MPRS. The government continued funding activities that have been perceived to have an impact on poverty reduction. The MPRS outlined a number of macroeconomic policies that have been adhered to achieve the macroeconomic targets. These policies have been mainly in the form of monetary, fiscal, and structural policies.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet